Broken Circle: Exploring Indigenous Perspectives of Academic Integrity - Cunningham Hall, Dawn (Canadian Perspectives on Academic Integrity, 2023)
Across the land now known as Canada, a growing body of research confirms the importance of academic integrity in higher education. Indigenous voices, though, are largely subsumed within the morass of dominant student and faculty perspectives or segregated alongside international student perspectives. Using the imagery of the Medicine Wheel as a framework, this session explores the views of Indigenous faculty, staff, administrators, and graduates affiliated with a mid-sized post-secondary institution in British Columbia. Findings from a small-scale research study reveal a holistic vision of academic integrity that emphasizes relationships with people and knowledge. As Wilson (2008) explains, “relationships do not merely shape reality, they are reality” (p.7). In this relational paradigm, academic integrity is inseparably grounded in the broader principles of integrity, and relies on reciprocal truth-telling to maintain the wholeness of the circle (Lindstrom, 2022). In this session, participants will gain insights into the ways dominant approaches to academic integrity can break the circle of integrity. The session will review similarities and differences between the experiences of Indigenous and non-Indigenous learners, and will consider how Indigenous views of relationality may foster a culture where stewardship of knowledge strengthens the bonds of integrity for all.